2003
DOI: 10.1074/jbc.m302244200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Up-regulates Prolyl Hydroxylase Activity

Abstract: The mechanism by which hypoxia induces gene transcription is now well established. Hypoxia reduces activity of prolyl hydroxylases (PHD) that hydroxylate specific proline residues in the oxygen-dependent degradation domain (ODD) of hypoxia-inducible factor-1␣ (HIF-1␣). As a consequence, HIF-1␣ accumulates and promotes hypoxic tolerance by activating gene transcription. This paper identifies the three forms of PHDs in rats and shows that a period of hypoxia selectively increases expression of PHD-2 mRNAs levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(90 citation statements)
references
References 20 publications
4
86
0
Order By: Relevance
“…Therefore, Hsp70 plays a predominant role in HIF-1␣ degradation specifically under conditions of prolonged hypoxia. PHD2 expression is also induced by hypoxia, and an earlier study concluded it does not promote HIF-1␣ degradation until cells are reoxygenated (34), whereas a recent study implicated PHDs in HIF-1␣ degradation during prolonged hypoxia (35). However, this mechanism cannot explain the differential stability of HIF-1␣ and HIF-2␣, as both proteins are negatively regulated by PHD2.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, Hsp70 plays a predominant role in HIF-1␣ degradation specifically under conditions of prolonged hypoxia. PHD2 expression is also induced by hypoxia, and an earlier study concluded it does not promote HIF-1␣ degradation until cells are reoxygenated (34), whereas a recent study implicated PHDs in HIF-1␣ degradation during prolonged hypoxia (35). However, this mechanism cannot explain the differential stability of HIF-1␣ and HIF-2␣, as both proteins are negatively regulated by PHD2.…”
Section: Discussionmentioning
confidence: 74%
“…The teleologic reason for the differential expression of PHD2 between fetus and adult is unclear, but may relate to the critical role of the PHDs upon reoxygenation (8,15,16) to ensure rapid cessation of the hypoxic response. Similarly, PHD2 mRNA and protein levels might be relatively high in the term mammalian fetus to ready the fetus to rapidly silence the HIF-1-dependent 21 experiments) PA SMC, hypoxia increased HIF-1 mRNA expression ( * , P Ͻ 0.01, versus normoxia), whereas in adult (n ϭ 8 animals; 24 experiments) PA SMC hypoxia had no effect on HIF-1 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…PHD2 likely has the dominant role (15), because ''silencing'' of PHD2 with siRNAs stabilizes and activates HIF-1␣ in normoxia, whereas silencing of PHD1 and PHD3 has no effect on the stability of HIF-1␣. PHD2 and PHD3 expression are up-regulated by hypoxia by HIF-1, providing an autoregulatory mechanism of HIF-1 stability driven by oxygen tension (16,17). Paradoxically, the expression of these hydroxylases is induced in hypoxic cell culture despite the fact that the reduced availability of the O 2 cosubstrate renders them inactive, suggesting that the PHD function to rapidly terminate the HIF-1 response upon reoxygenation (8,16).…”
mentioning
confidence: 99%
“…In the first instance, expression was defined at the mRNA level using RNase protection assays. Following reports of PHD mRNA regulation by hypoxia in certain cell lines (12,22,27,36), all cells were studied in normoxic culture and after exposure to hypoxia (0.5% oxygen) for 16 h. Fig. 1 shows results for cells derived from a variety of human tissues: BxPC-3 (pancreatic carcinoma); PC-3 (prostate carcinoma); MCF7, HS-587T, MDA-435, T47D, and ZR-75-1 (breast carcinoma); U-2 OS (osteosarcoma); OVCAR-3 (ovarian carcinoma); A549 (lung carcinoma); HT1080 (rhabdomyosarcoma); and JAR (choriocarcinoma).…”
Section: Phd Isoforms Manifest Distinct Patterns Of Cellular Expression-mentioning
confidence: 99%